2000
DOI: 10.1046/j.1365-3148.2000.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for irradiation of blood and blood components to prevent post‐transfusion graft‐vs.‐host disease in Japan

Abstract: The Japanese Red Cross analysed the results of questionnaires sent in 1993 regarding post-transfusion graft-vs.-host disease (PT-GVHD) from hospitals; the majority of patients with PT-GVHD in 1993 were transfused for cardiovascular or cancer surgery, and about 10 patients had died yearly from PT-GVHD in the following few years. The Japan Society of Blood Transfusion (JSBT) organized a subcommittee for the prevention of PT-GVHD, and issued a fourth version of guidelines for the irradiation of blood to prevent P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 15 publications
0
62
0
1
Order By: Relevance
“…Recently, allogeneic blood products for transfusion, such as RBC concentrates, platelet concentrates and plasma products, are usually used only after irradiation and leukocyte depletion by filtration [37]. Van de Watering et al [38] reported, in a large randomized controlled trial of patients undergoing cardiac surgery, that patients transfused leukocyte-depleted blood products by filtration before or after storage had fewer postoperative infections or mortality within 60 days after surgery than patients transfused standard packed cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, allogeneic blood products for transfusion, such as RBC concentrates, platelet concentrates and plasma products, are usually used only after irradiation and leukocyte depletion by filtration [37]. Van de Watering et al [38] reported, in a large randomized controlled trial of patients undergoing cardiac surgery, that patients transfused leukocyte-depleted blood products by filtration before or after storage had fewer postoperative infections or mortality within 60 days after surgery than patients transfused standard packed cells.…”
Section: Discussionmentioning
confidence: 99%
“…During storage, potassium content in irradiated blood tends to increase more quickly compared with routine, nonirradiated products, and the amount of potassium is correlated with the radiation dose. 23,29 Potassium load could be an important limiting factor for rapid, large-volume transfusions (exchange transfusions, intrauterine transfusions, etc) and if there is preexisting hyperkalemia. 25 It was shown that reactive oxygen species are increased in irradiated blood components in a dose-dependent and storage timedependent manner.…”
Section: Safety Of Irradiated Blood Productsmentioning
confidence: 99%
“…16 In countries with a high risk of TA-GVHD, blood product irradiation recommendations include more clinical scenarios where the patient is immunocompetent, and there may even be practices to universally irradiate all red blood cells and platelets in such environments (eg, Japan). 29 …”
Section: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations